2023
DOI: 10.1212/wnl.0000000000207664
|View full text |Cite
|
Sign up to set email alerts
|

Association of Very Early Treatment Initiation With the Risk of Long-term Disability in Patients With a First Demyelinating Event

Abstract: IntroductionEarly treatment is associated with better long-term outcomes in patients with a first demyelinating event and early multiple sclerosis (MS). However, magnetic resonance (MR) findings are not usually integrated to construct propensity scores (PS) when evaluating outcomes. We assessed the association of receiving very early treatment with the risk of long-term disability including an MR Score (MRS) in patients with a first demyelinating event.MethodsWe included 580 patients with a first demyelinating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Short delays in DMT initiation may increase the risk of long-term disability. 33 Our study suggests even relatively short DDs are associated with unfavourable consequences on disease activity. Although a greater relapse frequency was not observed in patients with a longer DD, these patients tended to have numerous risk factors associated with unfavourable disease outcomes, including a greater EDSS scores, lesion numbers on brain MRI and NfL levels, at MS diagnosis.…”
Section: Consequences Of Ddmentioning
confidence: 68%
“…Short delays in DMT initiation may increase the risk of long-term disability. 33 Our study suggests even relatively short DDs are associated with unfavourable consequences on disease activity. Although a greater relapse frequency was not observed in patients with a longer DD, these patients tended to have numerous risk factors associated with unfavourable disease outcomes, including a greater EDSS scores, lesion numbers on brain MRI and NfL levels, at MS diagnosis.…”
Section: Consequences Of Ddmentioning
confidence: 68%
“…However, the immunogenicity of vaccination can be compromised by immunosuppressive agents, particularly anti-CD20 therapies that are currently widely used . Consequently, clinicians eventually opt to delay the initiation of such therapies until vaccination schedules are completed, which could potentially have unfavorable consequences on the prognosis of the disease . Conversely, rapidly initiating anti-CD20 therapy without prior vaccination could potentially expose nonimmune people with MS (PWMS) to severe, vaccine-preventable infections.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study published in Neurology , investigators showed that very early treatment, within 6 months of onset of a first demyelinating event, was associated with lower rates of disability progression. 7 Similarly, in a large registry of patients with optic neuritis, early administration of immunomodulatory therapy was associated with less visual and disability progression. 8…”
mentioning
confidence: 98%
“…In a recent study published in Neurology, investigators showed that very early treatment, within 6 months of onset of a first demyelinating event, was associated with lower rates of disability progression. 7 Similarly, in a large registry of patients with optic neuritis, early administration of immunomodulatory therapy was associated with less visual and disability progression. 8 New methods to detect optic nerve dysfunction have emerged and were used in the study by Vidal-Jordana et al 5 Intereye differences in OCT by 5 μm for retinal nerve fiber layer and 4 μm for the ganglion cell and inner plexiform layer were previously shown to be important thresholds for establishing an optic nerve lesion.…”
mentioning
confidence: 98%